HILANGNYA ETIKA SEBAGAI SARANA ORIENTASI DAN KEBEBASAN EKSISTENSIONAL ELIT POLITIK - Litualy, Samuel Jusuf (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
Bertold Brechtâ€™s anecdote If Sharks Were Men tells us about the life in the sea between sharks and little fish. Sharks teach the little fish about moral and their obedience to sharks. If they always obey to the sharks, they will have better future. This anecdote describes the political elite as sharks. They are being described as people, who are thirst of authority, but on the other side teach the ordinary people about â€œmoralâ€. The ordinary people are being described as little fishes, that can be easily influenced and dominated. In this work, Brecht places himself as Mister K, the narrator, who lucidly describes the character of the ruler or political elite and the ordinary people. He makes three important points as a reflection of the life at that time. Firstly, the political elite always use the other people for their personal and group interest without feeling guilty, or in other words, public deception has already become a trend for political elite. Secondly, the ordinary people can be easily influenced to follow what Brecht calls in his work as â€œmoral teachingâ€. Thirdly, the character of political elite always deceive and ignore the people and the helplessness of the people in dealing with the ruler is seen in this work as a reflection of the loss of ethics as an orientation and of their powerlessness in enjoying their existential freedom.